A contribuição da afetividade no desenvolvimento da inteligência lógico-matemática - Rodrigues, Michele Aparecida Cerqueira (2021)
Affection in the transmission of knowledge serves as a basic tool when presenting, mainly, abstract order contents such as those presented in mathematics. In order to favor teaching and learning, the relationship of cognitive processes has been the central focus. For this, works where neuroscience was present were analyzed, since the process takes place in the brain. Having said that, there is an explanation about the understanding of human development and the importance of affectivity in the perception of Sigmund Freud and Jean Piaget. Next, an overview of theories, initially dedicated to giftedness, that can lead the individual to develop logical-mathematical intelligence through school enrichment processes that favor cognition and the assimilation of information is presented. Finally, the proposed activities help the teacher to develop skills related to critical thinking and logical reasoning inherent to this intelligence.